Protective effect of Salvianolic acid B against atherosclerosis: a preclinical systematic review and meta-analysis - Ji, Xing; Huang, Kailin; Lu, Aimei; Hu, Xiaomeng; Wu, Huanlin (Frontiers in Pharmacology, 2025)
BackgroundAtherosclerosis is the most common cause of cardiovascular disease, with high morbidity and mortality rates globally. Salvianolic acid B (Sal B), the most active and abundant component of the water-soluble extract of the traditional Chinese medicine Danshen, has been demonstrated to exert atheroprotective effects; nonetheless, its protective potential remains unclear. This study aimed to evaluate the preclinical efficacy of Sal B in the treatment of atherosclerosis and summarize the relevant mechanisms of action to provide evidence for its use in the treatment of atherosclerosis.MethodsA systematic search was conducted across eight databases, including PubMed, Embase, and Web of Science, etc., for studies related to Sal B in animal models of atherosclerosis, published from the inception of these databases up to November 2024. Parameters such as atherosclerotic lesion area, lipid deposition, plaque size, lipid metabolism, and changes in inflammatory markers were used to assess the extent of the atherosclerotic lesions. The SYRCLE risk-of-bias tool was used to determine methodological quality. Data were analyzed using the STATA software. Time-dose effect analysis was performed to explore the relationship between Sal B and atherosclerosis.ResultsEleven studies involving 275 animals were analyzed. The results of these studies indicate that Sal B has a significant positive impact on various indicators of atherosclerosis. A meta-analysis of preclinical studies showed that Sal B reduced atherosclerotic lesion area (P < 0.05), lipid deposition (P < 0.05) and plaque size (P < 0.05), lipid levels (TC, TG, LDL) (P < 0.05) and inflammatory responses (TNF-α, IL-6, IL-1β) (P < 0.05), as well as inhibiting phosphorylation of NF-κB and IκB proteins (P < 0.05). Time-dose interval analyses showed that Sal B was relatively effective at doses ranging from 2 to 100 mg/kg, with an intervention period of 4–14 weeks, administered either via gavage or intraperitoneal injection.ConclusionOur findings suggest that Sal B effectively delays the progression of atherosclerosis and represents a promising anti-atherosclerotic drug candidate. Further studies are required to translate these promising preclinical findings into the clinical treatment of atherosclerosis.